Patient‐relevant health outcomes for hemophilia care: Development of an international standard outcomes set. Issue 4 (6th March 2021) - van Balen, Erna C.; O'Mahony, Brian; Cnossen, Marjon H.; Dolan, Gerard; Blanchette, Victor S.; Fischer, Kathelijn; Gue, Deborah; O'Hara, Jamie; Iorio, Alfonso; Jackson, Shannon; Konkle, Barbara A.; Nugent, Diane J.; et al.
Abstract: Background: Patient‐relevant health outcomes for persons with hemophilia should be identified and prioritized to optimize and individualize care for persons with hemophilia. Therefore, an international group of persons with hemophilia and multidisciplinary health care providers set out to identify a globally applicable standard set of health outcomes relevant to all individuals with hemophilia. Methods: A systematic literature search was performed to identify possible health outcomes and risk adjustment variables. Persons with hemophilia and multidisciplinary health care providers were involved in an iterative nominal consensus process to select the most important health outcomes and risk adjustment variables for persons with hemophilia. Recommendations were made for outcome measurement instruments. Results: Persons with hemophilia were defined as all men and women with an X‐linked inherited bleeding disorder caused by a deficiency of coagulation factor VIII or IX with plasma activity levels <40 IU/dL. We recommend collecting the following 10 health outcomes at least annually, if applicable: (i) cure, (ii) impact of disease on life expectancy, (iii) ability to engage in normal daily activities, (iv) severe bleeding episodes, (v) number of days lost from school or work, (vi) chronic pain, (vii) disease and treatment complications, (viii) sustainability of physical functioning, (ix) social functioning, and (x) mental health. Validated clinical as well as patient‐reported outcome measurement instruments were endorsed. Demographic factors, baseline clinical factors, and treatment factors were identified as risk‐adjustment variables. Conclusion: A consensus‐based international set of health outcomes relevant to all persons with hemophilia, and corresponding measurement instruments, was identified for use in clinical care to facilitate harmonized longitudinal monitoring and comparison of outcomes.